OPTIMALISASI KERJA PETANI DALAM PENYIAPAN BIBIT PADI UNGGUL DENGAN INOVASI TEKNOLOGI TEPAT GUNA ALAT PENGUMPUL PADI - Junil Adri; Nelvi Erizon; Irzal Irzal (Unversitas Negeri Padang, 2020)
The purpose of carrying out this community service activity is to help farmers, especially Gapoktan Tunas Sakato, in the process of collecting rice in the process of preparing superior rice seeds for its members. Gapotan Tunas Sakato is an association of farmer groups in the village of Toboh Palabah. The centralization of the Tunas Sakato Gapoktan is to prepare seeds and control grain produced by farmers for distribution to local cooperatives. In this activity the community service team makes innovations that can help farmers in solving the problems they face. The community service team is planning to make a rice collection device. This tool will be able to make rice collection activities fast and efficient both in terms of energy and time. It will also be equipped with a direct packaging system. So the rice collected through this tool can be continued with the direct packaging process. The result of this activity was the creation of appropriate technology tools for rice collection machines. The public welcomed the arrival of this technology with great joy. The community service team performs an orerational demonstration of the tools to farmer groups in accordance with the specified operational standards. The community and farmer groups are happy to get this equipment because they are expected to be able to celebrate their work in the rice collection process